2016
DOI: 10.18203/2320-6012.ijrms20161927
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of ear discharge and antimicrobial sensitivity used in its treatment

Abstract: INTRODUCTIONEar discharge is any fluid that comes out from the external ear, also known as otorrhea. It could be in the form of blood, wax, pus or mucous fluid.Ear discharge is one of the cardinal symptoms of ear infection along with progressive deafness, pain, tinnitus and vertigo.Infection of the ear can be classified depending upon the site: otitis externa (infection of external ear) and otitis media (infection on middle ear). 1 Anatomy of the EARAs the matter of fact ear performs two sensory function: hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
1
0
0
Order By: Relevance
“…Similar results were also reported by Vaghela et al. 22 A possible reason for antibiotic resistance might be irrational use of antibiotics therefore, it was suggested that antibiotics must be used after performing susceptibility test and by doing this, the phenomenon of antibiotic resistance might be reduced to greater extent. Furthermore, Magnet et al 23 also described that genetic variation among bacterial isolates was the most significant reason for antibiotic resistance and also suggested that all these complications could be minimized up to some extent by maintaining hygienic condition in daily life.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were also reported by Vaghela et al. 22 A possible reason for antibiotic resistance might be irrational use of antibiotics therefore, it was suggested that antibiotics must be used after performing susceptibility test and by doing this, the phenomenon of antibiotic resistance might be reduced to greater extent. Furthermore, Magnet et al 23 also described that genetic variation among bacterial isolates was the most significant reason for antibiotic resistance and also suggested that all these complications could be minimized up to some extent by maintaining hygienic condition in daily life.…”
Section: Discussionsupporting
confidence: 85%
“…Using sterile syringes 1ml of each isolates was inoculated in small discs on solidified Muller Hinton Agar plates containing 1ml of earwax concentrations each. These plates were labelled as corresponding to the cerumen (Vaghela et al, 2023). Then all the plates were incubated at 37°C for 48hours.…”
Section: Manuscript Draftmentioning
confidence: 99%